A genetic variant in the gene encoding fibrinogen beta chain predicted development of hypertension in Chinese men - Ong, Kwok Leung; Tso, Annette W. K.; Cherny, Stacey S.; Sham, Pak Chung; Lam, Karen S. L.; Jiang, Chao Qiang; Thomas, Neil G.; Lam, Tai Hing; Cheung, Bernard M. Y (Thrombosis and Haemostasis, 2010)
Fibrinogen, a major determinant of blood viscosity, is an acute phase protein associated with cardiovascular disease. We studied the association of hypertension with single nucleotide polymorphisms (SNPs) in the gene encoding the fibrinogen β chain (FGB). Three tagging SNPs (rs1025154, rs4220 and rs1044291) were selected from the HapMap database on Han Chinese. Genotypes were determined in 1,294 unrelated subjects from the Hong Kong Cardiovascular Risk Factor Prevalence Study cohort. There were 199 hypertensive subjects at baseline. Among 1,095 subjects normotensive at baseline, 178 developed hyper-tension during a median follow-up period of 6.4 years. Among the three tagging SNPs, rs4220 showed significant association with hypertension at both baseline (odds ratio [OR]=1.49, p=0.004) and at follow-up (OR=1.32, p=0.013). The minor A allele of this SNP was associated with higher plasma fibrinogen level (β=0.144, p<0.001 at baseline and β=0.130, p<0.001 at follow-up). Among subjects normotensive at baseline, this SNP was also associated with the development of hyper-tension in men (OR=1.52, p=0.022), but not in women. The SNP rs4220 in FGB, which leads to the substitution of arginine by lysine at position 448, is independently associated with plasma fibrinogen level and hypertension in Hong Kong Chinese. This suggests a possible causal role of fibrinogen in hypertension development, especially in men.
Keywords: Fibrinogen; hypertension; single nucleotide polymorphisms